1999
DOI: 10.1016/s0273-1223(99)00639-3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of humic substances by coagulation

Abstract: The efficiency of humic acid removal by coagulation and 2-hour sedimentation was studied. The investigations also included determination of optimum pH for removing humic and fulvic acids from aqueous solutions (pH = 6.0 or > 10.0). The experiments show that 1) ferric sulphate is less efficient than alum, and 2) Al3ł and Fes+ act as coagulants and coordinating ions for metal-organic complexes and are removed together with humic acids. NOTATION А1residual concentration of aluminium ions, -coloured matter [g Pt/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A significantly greater effectiveness of the oxidisation of Fe(II) to Fe(III) and its removal in the sedimentation process was obtained as a result of chemical oxidisation by means of potassium manganate (VII) or chlorine dioxide, when low-molecular and not highmolecular compounds were dominant among the organic ligands as part of the iron-organic complex. One of the ways recommended for intensifying the removal of iron that occurs in a form of stable ferro-organic compounds is application of the coagulation process, preferably with aluminium salt (Krupińska 2012;Albrektiene et al 2011;Libecki, Dziejowski 2010;Libecki, Dziejowski 2008;Potgieter et al 2005;O'Melia et al 1999;Huang, Shiu 1996;Jekel 1986;Dempsey et al 1984). It has also been found that polymerised polyaluminium chlorides are more effective at removing organic substances and reducing turbidity than aluminium sulphate (VI) (Krupińska 2014;Eikebrokk, Fettig 1990;Dempsey et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…A significantly greater effectiveness of the oxidisation of Fe(II) to Fe(III) and its removal in the sedimentation process was obtained as a result of chemical oxidisation by means of potassium manganate (VII) or chlorine dioxide, when low-molecular and not highmolecular compounds were dominant among the organic ligands as part of the iron-organic complex. One of the ways recommended for intensifying the removal of iron that occurs in a form of stable ferro-organic compounds is application of the coagulation process, preferably with aluminium salt (Krupińska 2012;Albrektiene et al 2011;Libecki, Dziejowski 2010;Libecki, Dziejowski 2008;Potgieter et al 2005;O'Melia et al 1999;Huang, Shiu 1996;Jekel 1986;Dempsey et al 1984). It has also been found that polymerised polyaluminium chlorides are more effective at removing organic substances and reducing turbidity than aluminium sulphate (VI) (Krupińska 2014;Eikebrokk, Fettig 1990;Dempsey et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the previous work in NOM research has been carried out on optimizing NOM removal using metal salts in terms of the amount of coagulant added and the coagulation pH ( ) and how the change in character of NOM impacts on the treatment performance ( ). The work carried out on NOM flocs has concentrated on how these fragile structures may be quantified and how flocs may change from season to season with variable water quality ( , ).…”
Section: Introductionmentioning
confidence: 99%
“…liquid chromatography-organic carbon detection LC-OCD, 25 are a fraction of DOC that are well-removed during coagulation treatment. 19,[26][27][28][29] SUVA and HS/DOC are reportedly good indicators of treatability. 27 DOC concentrations and character vary on a range of timescales, including seasonal, daily, and sub-daily through changing source areas and in-stream processes.…”
Section: Introductionmentioning
confidence: 98%